2011
DOI: 10.1161/cir.0b013e318233bc6a
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adiposity

Abstract: T he prevalence of obesity in the United States and the world has risen to epidemic/pandemic proportions. This increase has occurred despite great efforts by healthcare providers and consumers alike to improve the health-related behaviors of the population and a tremendous push from the scientific community to better understand the pathophysiology of obesity. This epidemic is all the more concerning given the clear association between excess adiposity and adverse health consequences such as cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
368
0
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(396 citation statements)
references
References 292 publications
(279 reference statements)
6
368
0
22
Order By: Relevance
“…A striking result from the study was the emergence of abdominal obesity, which increases risk of many chronic diseases independently of total adiposity (11)(12)(13) , particularly among women during follow-up. While weight gain might be expected, presence of abdominal obesity is among the first indications of detrimental metabolic changes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A striking result from the study was the emergence of abdominal obesity, which increases risk of many chronic diseases independently of total adiposity (11)(12)(13) , particularly among women during follow-up. While weight gain might be expected, presence of abdominal obesity is among the first indications of detrimental metabolic changes.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence mainly from Caucasian populations and cross-sectional studies indicates that abdominal obesity (waist circumference (WC): men $102 cm; women $88 cm), which affects approximately two-fifths (men: 29 %; women: 48 %) of adults worldwide (9) and 53 % of US adults (10) , may be of greater importance in increasing morbidity and mortality risk than total obesity (11)(12)(13) . Additionally, abdominal obesity is a key component of the metabolic syndrome, a clustering of cardiometabolic risk factors which includes abdominal obesity, hypertension, low HDL-cholesterol, hypertriacylglycerolaemia and hyperglycaemia (14) .…”
mentioning
confidence: 99%
“…Although the VFA at the umbilicus has been widely used to identify visceral obesity13, 14, 15, 16, 17, 18, 19, we previously showed that the maximal VFA was not at the umbilicus, but was widely distributed from L1 to L520, 21.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, the Japan Society for the Study of Obesity (JASSO) has recommended that the appropriate cut‐off values of WC for detecting visceral obesity are 85 cm in Japanese men and 90 cm in Japanese women from the general population12, and these values are widely used for diagnosis of MetS in Japan. As the JASSO cut‐off value of WC is higher for women than men, unlike the criteria used in other Asian countries, reassessment of the cut‐off values for Japanese persons has been carried out previously, and different values have been proposed13, 14, 15, 16, 17, 18, 19. However, these previous Japanese studies were based on WC and/or the visceral fat area (VFA) at the umbilicus determined by CT scanning.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the estimated annual direct cost for CVD and stroke in the United States was about $196 billion 1. Incidence, associated morbidity, disability, mortality, and healthcare costs have been shown to depend largely on modifiable risk factors (MRFs) for CVD 3, 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%